Grammar and Plagiarism Checking for English Learners: The Case of Grammarly Users - phuangsuwan, penpim; Siripipatthanakul, Supaprawat; Limna, Pongsakorn; Siripipattanakul, Sutithep (วารสารรัฐศาสตร์รอบรู้และสหวิทยาการ, 2024)
Abstract: In recent decades, digital technology and artificial intelligence (AI) have evolved dramatically, and there have been an increasing number of applications to support language instruction effectively, and English writing skill teaching in particular: the qualitative documentary study and content analysis were used in the literature review. The literature review was conducted using the following databases: EBSCO, Google Scholar, Scopus, Web of Science, and ScienceDirect. Purposive sampling was employed to undertake six interviews with a university student majoring in English in Thailand. Semi-structured interviews were employed. Content analysis of credible and legitimate sources was made. NVivo was used to analyze the literature review data. The findings reveal that all students perceived that English proficiency via communication and writing could improve their skills if they used Grammarly to generate articles with numerous unique ideas and correct grammar and if lecturers encouraged students to use Grammarly to instruct and learn. From the same perspective, Grammarly is one of the educational technology devices that impacts students' writing, both what they write and how they write. AI has made it easier for students to prepare, write, and edit themselves. Many tools have been developed to enhance the process of teaching and learning writing due to the problems that students have in learning how to write and the benefits of employing technology in language instruction. Grammarly is one such AI tool for educational technology in English academic writing. This software is frequently used at many colleges and institutions worldwide and is thought to be helpful. Based on the practical demands and the utility of Grammarly, some valuable advice is provided for adequately utilizing the programme to reduce students' writing errors and avoid plagiarism. The recommendation is to consider a quantitative questionnaire for general explanation in further study.